Trivialization, Predicate and Nominalization - Miranda Rojas, Rafael Felipe (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The present paper aims to discuss the scope of the rigidity of the general terms through the so-called predicative via. In particular, it will be analized the interpretation of Zerbudis (2013) about the proposal developed by Salmon (2005). It will be shown how both positions, while dependent on a predicative reading of rigidity in general terms, do not respond to the initial kripkean desideratum. Following López de Sa (2008a, 2008b) it argues that the nominal via (or nominalization) avoids the problems arising from a reductive predicative reading (general terms only fulfill the role of predicate). Specifically, it is argued that the nominal reading allows to understand how theoretical statements of identity are not at risk of trivialization. From the case the color of the sky, it is observed that the admission of contingent identity (CI) obviates a central thesis of Kripke’s proposal: the necessity of identity.
Keywords: trivialization; nominalization; predicative via; contingent co–referentiality; rigid co–referentiality